Aetiology of Coexisting Mental Health and Alcohol and Other Drug Disorders: Perspectives of Refugee Youth and Service Providers. (April 2015) - Posselt, Miriam; Procter, Nicholas; Galletly, Cherrie; de Crespigny, Charlotte
<x xml:space="preserve">Abstract</x> In the general population, people with comorbid mental health (MH) and alcohol and other drug (AOD) disorders (comorbidity) have great difficulty accessing appropriate services, and poor outcomes. Little is known about comorbidity in resettled refugees in Australia. This study was designed to identify risk factors and patterns of comorbidity development in young people from refugee backgrounds living in a disadvantaged urban region of Adelaide, South Australia. This qualitative study utilised in‐depth semi‐structured interviews (n = 30) with resettled refugee youth and workers from MH, AOD, and refugee support services. Thematic analyses were conducted to investigate the aetiology of MH and AOD disorders in young refugees. Interviews with both groups revealed how the interrelated nature of risk factors may place young people from refugee backgrounds at heightened risk of experiencing MH and AOD problems. The situations and conditions described by both groups are discussed under six main themes: pre‐migration experiences of torture and trauma; familial factors of intergenerational conflict; post‐migration adjustment difficulties in terms of language, culture, education, and employment; exposure to and availability of substances; maladaptive coping strategies and self‐medication; and access to information and services. Implications for psychologists and MH professionals are identified, emphasising the need for clinicians to understand the complexities surrounding the aetiology of comorbidity in these youth. The initial assessment needs to be comprehensive, including pre‐ and post‐settlement experiences and cultural and family dimensions of their current situation. Treatment may often need to simultaneously address multiple contributing factors and involve culturally sensitive psycho‐education.